Understanding payment switching behavior to QRIS in Southwest Papua: A push-pull-mooring study - Hidayah, Nurul; Iriani, Latifah Dian (Universitas Muhammadiyah Yogyakarta, 2025)
As the global economy changes, it's important to examine why people in Southwest Papua switch from cash to the Quick Response Code Indonesian Standard (QRIS) system. This region is notoriously behind in infrastructure and human development, so studying this area is crucial to expanding the national economy. This study investigates the variables that influence the switching behavior of users in Southwest Papua toward the Quick Response Code Indonesian Standard (QRIS) digital payment. The study investigates the impact of push factors (e.g., perceived trouble, perceived no record for transactions, and difficulty paying cash in large amounts), pull factors (e.g., perceived convenience, promotional benefits, and time savings), and mooring factors (e.g., habit and switching costs) on the transition from cash to digital payments, utilizing the Push-Pull-Mooring (PPM) framework and transaction cost theory. The research uses a method called structural equation modeling to study how QRIS users behave in three areas of Southwest Papua Province: Sorong City, Sorong Regency, and Raja Ampat, by selecting participants randomly from different groups. The results indicate that the adoption of QRIS is significantly influenced by both push and pull factors, with pull factors playing a more prominent role. Habit also significantly influences switching behavior, while switching costs show a negative but statistically insignificant effect. To expedite the adoption of digital payments in Southwest Papua, these insights provide policymakers and financial institutions with practical advice. They indicate that strategies that emphasize the convenience and advantages of QRIS over cash are more effective in increasing user adoption.